UMP commemorates services and contributions of retirees - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 30 December 2021 - Universiti Malaysia Pahang (UMP) organised Majlis Jasa Dikenang to commemorate the services of retirees while serving at the university.